Strategi Pengembangan Koperasi Desa Merah Putih: Tinjauan Literatur atas Praktik Terbaik dan Tantangan Global - Syarifuddin Arief; Haeruddin Haeruddin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
The Merah Putih Village Cooperative program is a strategic initiative launched by the Indonesian government to promote rural economic independence through cooperative institutions. This study aims to review and synthesize development strategies for village cooperatives using a systematic and narrative literature review approach. Data sources include accredited national journals, institutional reports, and reputable international publications from 2015 to 2024. The findings reveal five dominant strategic themes: (1) strengthening cooperative institutional capacity through good and transparent governance; (2) developing human resources through structured training and cooperative education; (3) utilizing technology and digitalization to improve operational efficiency and market access; (4) enhancing community participation and empowerment as the foundation for cooperative sustainability; and (5) policy support from the government and synergy with external stakeholders. This study concludes that developing village cooperatives requires an integrated and participatory approach that considers local context, institutional capacity, and technological readiness. The insights from this review are expected to serve as a reference for policymakers, cooperative practitioners, and academics in designing competitive and sustainable village cooperatives.